Probability and statistics for engineers - Johnson, Richard A. (Pearson, 2014)
This example-rich exploration of both elementary probability and basic statistics places a strong emphasis on engineering and science applications. Coverage explores the treatment of data; probability; probability distributions; probability densities; sampling distributions; inferences concerning means; inferences concerning variances; inferences concerning proportions; nonparametric tests; curve fitting; analysis of variance; factorial experimentation; the statistical content of quality-improvement programs; and applications to reliability and life testing. For practicing engineers or anyone interested in probability and statistics